Quality education challenges, effects and lessons of the COVID-19 pandemic among selected college students in UPVTC - Mangada, Mickyle Jeob L.; Montesclaros, Ruth Mae M. (2022)
The unprecedented occurrence of the COVID-19 pandemic has challenged the operations of academic institution's delivery of quality education to their learners. The sudden implementation of distance learning in the country has undoubtedly compromised learning competencies and the student's welfare as well as it has hampered the essence of optimal instruction and academic excellence. To shed light on the existing condition of quality education in a national university-- University of the Philippines Visayas Tacloban College, the researchers conducted a mixed method study to a.) describe the challenges experienced by college students during distance learning, b.) to analyze the different adaptation strategies employed by college students during distance learning; and c.) determine the factors affecting the academic performance of college students during distance learning. Regression analysis revealed that as the socioeconomic status, stability of internet connection, overall distance learning experience, course mastery, mental health, and learning resource accessibility increase, the academic performance or the general weighted average of students increases by 0.00109, 0.03590, 0.000371, 0.00330, 0.001611, and 0.02081 units respectively. Meanwhile, as the access to devices increases, the academic performance or the general weighted average of students decreases by 0.01528 units. The results of the content analysis revealed that students have available yet do not have complete accessibility to necessary and reliable resources for online learning. Furthermore, the inability to distinguish school-home boundaries and mental health problems have been recurring issues for most students. More importantly, despite the relatively higher grades that students have received in this learning modality, methods employed in distance learning have proved to be lacking and inefficient for most students. Students feel that there is a disconnect and a gap that they are not genuinely learning the necessary skill sets to survive and excel in their future profession.